The Rise of Service Employment in the Canadian Economy - Magun, Sunder (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This paper analyzes the trends in employment shares by industry and presents an employment profile of the service-producing and goods-producing sectors and examines some of the reasons for the shift to service jobs.